(untitled) (Central Asian Journal of Medical Sciences, 2017)
Objectives: Lagotis integrifolia (Willd.) Schischk is an ingredient in many traditional Mongolian medicine prescriptions used for the treatment of hot-natured disorder, impure blood caused disorder, disorders of the vital organs, diphtheria, anthrax, and pneumonia. The objective of this study was to isolate and identify the compounds contained in Lagotis integrifolia. Methods: The compounds were isolated and purified using column chromatography, crystallization, and recrystallization methods. Chemical structures were elucidated using MS, 1H, 13C, HSQC, HMBC, and 1H-1H COSY NMR. Results: We identified 7-dihydroxy-2-(3-hydroxy-4-methoxyphenyl) chromen-4-one (diosmetin), luteolin-7-O-glucopyranoside (cynaroside), and mannitol. Conclusion: Diosmetin and cynaroside were obtained from Lagotis integrifolia for the first time in Mongolia.